2008
DOI: 10.1126/science.1155888
|View full text |Cite
|
Sign up to set email alerts
|

VelB/VeA/LaeA Complex Coordinates Light Signal with Fungal Development and Secondary Metabolism

Abstract: European temperate forests (such as to tropical forests or to plant species other than trees). Moreover, if seed-dispersing animals are as crucial to the persistence of plants as this and other studies suggest (28, 29), then the combination of habitat loss with direct and indirect removal of animals, to which many of the world's most diverse forests are subject, is likely to have more drastic effects than either perturbation alone. In these circumstances, animaldispersed species might be more, not less, sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
965
4
21

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 804 publications
(1,014 citation statements)
references
References 24 publications
(1 reference statement)
24
965
4
21
Order By: Relevance
“…SasA interaction to other proteins was analyzed by tandem affinity purification (TAP), which allows identifying large relatively stable protein complexes (Bayram et al, 2008;Gavin et al, 2002). This might include proteins which only indirectly interact with SasA if several proteins of the same metabolic or developmental pathway form large complexes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SasA interaction to other proteins was analyzed by tandem affinity purification (TAP), which allows identifying large relatively stable protein complexes (Bayram et al, 2008;Gavin et al, 2002). This might include proteins which only indirectly interact with SasA if several proteins of the same metabolic or developmental pathway form large complexes.…”
Section: Discussionmentioning
confidence: 99%
“…TAP experiments were performed as described previously (Bayram et al, 2008) with the TAP-tagged protein strain and the untagged wild type strain as control. In addition to the standard protocol, modified purifications were performed.…”
Section: Tandem Affinity Purification (Tap)mentioning
confidence: 99%
See 2 more Smart Citations
“…Relevantly, it has been observed that the production of CAZymes and proteases depends on functional regulators BcVEL1 and BcLAE1, in Botrytis cinerea, which are the A. nidulans orthologs of VeA and the SAM-dependent methyltransferase LaeA, respectively [55]. In A. nidulans, VeA and LaeA form a trimeric complex with another member of the velvet protein family, VelB, and this complex is responsible for the regulation of secondary metabolism and development [56]. Apart from functionality in secondary metabolism, LaeA in A. nidulans also controls expression of carbohydrate metabolism enzymes such as Hülle cell specific α-mutanase, which is involved in establishment of fully mature fruiting bodies [57].…”
Section: Discussionmentioning
confidence: 99%